2018
DOI: 10.12806/v17/i3/r9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing self-efficacy through immersive simulations: Leading professional learning communities

Abstract: Research suggests effective immersive simulations that rely on augmented reality enhance teachers' self-efficacy and skills (Badiee & Kauffman, 2015). However, there is a gap in the literature as studies have largely ignored their uses in educational leadership programs (Bradley & Kendall, 2015). This study investigated the relationship between application of critical skills within an immersive simulation environment and 26 school or district leaders' perceptions of self-efficacy in leading a professional lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Graduate students practiced leading professional learning communities with the use of an immersive classroom simulation and reported an increase in self-efficacy ratings, as measured by feelings of confidence doing certain tasks, following the simulation. 16 The researchers found that two forms of immersive learning had similar effects: mastery experiences and vicarious learning. Participants who were actively practicing in the immersive environment reported increased self-efficacy as well as participants who watched the immersion passively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Graduate students practiced leading professional learning communities with the use of an immersive classroom simulation and reported an increase in self-efficacy ratings, as measured by feelings of confidence doing certain tasks, following the simulation. 16 The researchers found that two forms of immersive learning had similar effects: mastery experiences and vicarious learning. Participants who were actively practicing in the immersive environment reported increased self-efficacy as well as participants who watched the immersion passively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scenarios were realistic reflections of professional meetings and differed based on random selection of avatar behavior and then in accordance with participant responses to avatar behavior. The quantitative and qualitative data collected from the study showed a statistically significant increase in participant confidence and comfort in assessing group dynamics and decision making and in handling difficult situations (Gilbert et al., ).…”
Section: Ar In the Classroommentioning
confidence: 99%
“…Research has shown that when they are removed from the cognitive load of having to actively work through a task, students can more easily process lessons learned from a scenario by observing (Hoover, Giambatista, & Belkin, ). In addition, group discussion of the scenario “often deconstructed the status quo, encouraged collaborative construction [on] more effective approaches, and increased participants’ willingness to try these new approaches” (Gilbert et al., , p. 166). Overall, by expanding practice opportunities, improving efficiency of practice, and creating opportunities to observe others, AR learning scenarios are more effective than limited live practicum sessions (Badiee & Kaufman, ).…”
Section: Ar In the Classroommentioning
confidence: 99%
See 2 more Smart Citations